(untitled) (Communications in Computational Physics, 2018)
We propose a direct imaging method based on reverse time migration (RTM) algorithm for imaging extended targets using electromagnetic waves at a fixed frequency in the rectangular waveguide. The imaging functional is defined as the imaginary part of the cross-correlation of the Green function for Helmholtz equation and the back-propagated electromagnetic field. The resolution of our RTM method for penetrable extended targets is studied by virtue of Helmholtz-Kirchhoff identity in the rectangular domain, which implies that the imaging functional always peaks in the target. Numerical examples are provided to demonstrate the powerful imaging quality and confirm our theoretical results.